Morphological diversity of phytolith structures in six species of Carex L. and Cyperus L. (Cyperaceae Juss.) from West Bengal, India - SUBRATA MAJUMDER; TANMOY MALLICK; Asok Ghosh (Society for Indonesian Biodiversity, 2020)
Abstract. Majumder S, Mallick T, Ghosh A. 2020. Morphological diversity of phytolith structures in six species of Carex L. and Cyperus L. (Cyperaceae Juss.) from West Bengal, India. Biodiversitas 21: 3471-3486. Cyperaceae is a taxonomically challenging group due to its cosmopolitan distribution, similar vegetative structure, and reduced reproductive morphology. The present study focused on the characterization and description of phytolith morphotypes based on shape, structure, and ornamentation. Six species of Carex L. and Cyperus L. (three species each) were considered for the present study. From the investigation, we found 56 phytolith morphotypes, among which the principle ones were conical, elongate bulbous margin, lanceolate psilate, tabular concave with verrucate, tabular concave columellate, ovate granulate, and orbicular concave. The conical morphotype was most commonly found. The elongate bulbous margin, lanceolate psilate, and tabular concave with verrucate phytolith morphotypes were specific to the genus Carex, while the tabular concave columellate, ovate granulate and orbicular concave were only found in Cyperus spp. Further, the detailed study of conical morphotypes revealed a distinctive character among the studied genera. Our study concludes that conical, elongate bulbous margin, lanceolate psilate, tabular concave with verrucate, tabular concave columellate, ovate granulate, and orbicular concave morphotypes are constant at the genus level and may play a role in taxonomic identification in the family Cyperaceae.